Effects of stretching warm-up exercises in performance of specific track and field power events - Meyer, Lowell (My University, 1972)
This study was designed to compare the effects of warm-up on performance of tenth grade boys in the running long jump, forty yard dash, and shot put. An attempt was made to determine whether or not warm-up was c; of value in improving performance of the running long jump, forty yard, and the shot put. The subjects were forty-one tenth grade boys enrolled in a required physical education class at Lincoln High School, Wisconsin Rapids, Wisconsin. The subjects were members of an intact physical education class. The group members followed a specific program of performance in the running long jump, forty yard dash and shot put with and without preliminary warm-up exercises for an eight week period. The statistical technique used to indicate differences in mean scores on the warm-up and non warm-up performance for each test was a t-test for non-independent groups. The five percent level of confidence was used for acceptance or rejection of the null hypotheses. Values for "t" indicated that there were no significant differences in the warm-up and non warm-up scores for the running long jump, forty yard dash, and shot put. The results of this study indicate that preliminary stretching warm-up exercises as administered in this study to tenth grade boys will not significantly improve performance of the running long jump, forty yard dash, and shot put.